Evaluation of NaCl Effect on Vibration-Delaminated Metal-Polymer Composites by Improved Micro-Raman Methodology - E. Zumelzu; I. Asomavich; F. Rull; C. Cabezas (Journal of Spectroscopy)
Polyethylene terephthalate (PET) is a polymer coating that protects the electrolytic chromium coated steel (ECCS) against aggressive electrolytes like NaCl. It is widely accepted by manufacturers that NaCl has no effect on the PET coating, which is inert. However, we showed that there are some effects at the structural level, caused by vibrations, and facilitated by defects on the layers. The vibrations occurring during the transportation of food containers produce delaminations at given points of the metal-polymer interface, known as antinodes, which in turn may produce PET degradation affecting food quality. The former can be determined by electrochemical measurements, and the changes in composition or structural order can be characterized by Raman. The present work applied this latter technique in experimental samples of PET-coated ECCS sheets by performing perpendicular and parallel analyses to the surface, and determined that it constitutes a new potential methodology to determine the behavior of the composite under the above conditions. The results demonstrated that the delamination areas on the PET facilitated polymer degradation by the electrolyte. Moreover, the Raman characterization evidenced the presence of multilayers and crystalline orderings, which limited its functionality as a protective coating.